CMSP suppresses oral squamous cell carcinoma progression by targeting the JAK2/STAT3/c-Myc axis - Lu, Yueting; Yao, Manman; Wang, Dixian; Higuchi, Daisuke; Lu, Hualin; Shang, Hongyue; Dong, Bo; Zhang, Jiao; Jin, Ruizhe; Liu, Tiejun (Frontiers in Oncology, 2025)
BackgroundOral squamous cell carcinoma (OSCC) is a highly invasive head and neck malignancy with poor prognosis and limited treatment efficacy. This study aimed to investigate the anti-tumor potential of p-hydroxycinnamaldehyde (CMSP), a bioactive compound derived from the traditional Chinese and Mongolian medicinal herb Momordica cochinchinensis.MethodsThe effects of CMSP on OSCC were evaluated in vitro using CAL27 and SCC15 cell lines and in vivo in a CAL27 xenograft nude mouse model. Cell proliferation, migration, and invasion were assessed by CCK-8 and transwell assays. Flow cytometry was used to analyze cell cycle and apoptosis. Transcriptomic sequencing followed by KEGG and GO enrichment analyses was performed to identify key regulatory pathways, and Western blotting was used to validate protein expression. Bioinformatics and molecular docking analyses were further conducted to explore CMSP–target interactions.ResultsCMSP inhibited proliferation, migration, and invasion of OSCC cells in a dose-dependent manner, induced S-phase arrest, and promoted apoptosis. Transcriptomic and enrichment analyses identified the JAK2/STAT3 signaling pathway as a major target. Western blotting confirmed that CMSP significantly suppressed phosphorylation of JAK2 and STAT3 and downregulated downstream c-Myc expression. In vivo, CMSP markedly reduced tumor growth in nude mice. Bioinformatics and molecular docking suggested that MYC-related signaling contributes to the anti-tumor activity of CMSP in OSCC.ConclusionCMSP exerts anti-OSCC effects, at least in part, through modulation of the JAK2/STAT3/c-Myc signaling axis, and may serve as a promising adjunctive therapeutic candidate for OSCC management.